Applying Risk Indices to Assess and Manage Soil Salinization and Sodification in Crop Fields within a Mediterranean Hydro-Agricultural Area - Tomaz, Alexandra (2022)
Irrigation-induced or secondary salinization can occur when salts are introduced by irrigation water and accumulate within the root zone due to insufficient leaching. Mediterranean regions are especially susceptible, given the predominant climate and the expanding of irrigation areas. In this study, two indices to assess the risk of salinization (RSA) and sodification (RSO), previously applied at a regional scale, were used in a hydro-agricultural area (AHA) in Southern Portugal, in ten crop fields. Information on climate, irrigation water quality, soil characteristics, and land use was obtained from large databases and from local data. The results revealed the feasibility of using the RSA and RSO indices both on large and smaller scales, seeing as most of the area in the monitored crop fields presented the same risk classes (62% in RSA and 78% in RSO). Deviations were due to the reduction in scores for drainage and, in the case of RSO, the assigned irrigation method based on the land occupation class. Considering that different spatial scales of risk assessment are associated with different objectives and management options, a risk management framework was outlined following a multi-scale perspective for mitigation actions in salt-sensitive areas, ranging from territorial planning to the adoption of on-farm practices that can contribute to the sustainability of irrigated agriculture.